Penggunaan Mikroorganisme Dalam Biokontrol Hama Tanaman Use Of Microorganisms In Plant Pest Biocontrol - Gea, Fitri Julianti; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
Biological control of plants is a way of managing pests and diseases by utilizing living organisms, such as predators, parasites, parasitoids, or microorganisms, including bacteria, fungi, and viruses. The aim is to reduce the population of plant pest organisms (OPT) Hasyim,dkk. (2015). This method is applied to maintain ecosystem balance, minimize the use of chemical pesticides, and support sustainability and environmental health in agricultural systems. This research employs a literature study technique, which attempts to locate, investigate, assess and interpret various important research.